Obtaining Bio-Hydrogen from Palm Oil Mill Effluent (POME) - A Preliminary Evaluation - Mohamad Mokhtar, Ibrahim; Zulkifly, Jemaat; Nour, Abdurahman Hamid (Trans Tech Publications, 2021)
A complete set-up of obtaining bio-hydrogen from palm oil mill effluent (POME) was successfully demonstrated in this study. The proposed set-up is a combination of upflow anaerobic sludge blanket (UASB) bioreactor (POME is digested to obtain methane) and subsequent a dry reforming tubular reactor (conversion of methane into bio-hydrogen). The UASB reactor with 10 litres working volume was operated in continuous operation at mesophilic temperature (38 °C), pH was maintained between 6.5 and 7.2 by adding buffering solution containing of 5 gL-1 of calcium oxide (CaO) and hydraulic retention time (HRT) was set at 1 day. Prior to feeding of POME, the UASB reactor was inoculated with sludge taken from anaerobic pond at Lepar Hilir Palm Oil Mill. Then, the reactor was continuously fed with the raw POME with COD concentration of 7,773 mgL-1 and organic loading rate (OLR) of 7.61 g CODL-1d-1. Meanwhile the dry reforming fixed-bed tubular reactor was operated at 750 °C and 0.1 g catalyst type Ni/SBA-15. Biogas produced from the UASB reactor was fed into the tubular reactor and gas samples were collected at the inlet and outlet and analyzed using GC-TCD. On average, the UASB reactor produced about 32 Ld-1 biogas containing of 80 % methane and removing 67 % of COD. This biogas was fed into the dry reforming rector and the reaction took place in the reactor produced about 32 % of H2, 0.24 % of CH4, 28 % of CO2 and 39 % of CO. This result yielded a H2/CO ratio close to 1, demonstrated an efficient route for producing bio-hydrogen gas. Meanwhile, CH4 conversion was recorded at 99.7 %.